Konsep Etika Pendidikan Islam dalam Naskah Puspakerme Perspektif Teori Semiotika Ferdinand De Saussure - Junaedi, Hartono; Jamaludin, Jamaludin; Satriawan, Lalu Agus; Bagas, Muh Ali (Arfannur: Journal of Islamic Education, 2025)
This study aims to explore the concept of Islamic education ethics in the Puspakerme manuscript from the perspective of Ferdinand De Saussure's semiotic theory. The type of research used is library research using a semiotic approach. The primary data source in this study is; translated books of the Puspakerma manuscript. The data analysis used is content analysis and semiotics. The results of the study indicate that the concept of Islamic education ethics in the Puspakerma Manuscript is based on three types of concepts, namely; First, the concept of Islamic education ethics which is theocentric or self-serving to God Almighty and the Prophet Muhammad SAW the beloved of Allah, because of this attitude, faith , knowledge and charity are formed for the salvation of the world and the hereafter ; Second, it is anthropocentric which is divided into three parts, namely; Family ethics, teacher and student ethics, and community ethics; Third, it is cosmocentric. This ethical concept is divided into three parts, the same as anthropocentric ethics. The three parts in question are; ethics towards nature, ethics towards animals, and ethics towards plants.